2020
DOI: 10.1101/2020.09.04.20165340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence for differential gene expression in major depressive disorder PBMCs, but robust evidence of elevated biological ageing

Abstract: Background The increasingly compelling data supporting the involvement of immunobiological mechanisms in Major Depressive Disorder (MDD) might provide some explanation of the variance in this heterogeneous condition. Peripheral blood measures of cytokines and chemokines constitute the bulk of evidence with consistent meta-analytic data implicating raised proinflammatory cytokines such as IL6, IL1β and TNF. Among the potential mechanisms linking immunobiological changes to affective neurobiology is the accelera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
2
4
1
Order By: Relevance
“…These results are consistent with prior studies showing associations between multiple psychiatric phenotypes, including PTSD, AUD, MDD, and anxiety, and advanced DNAm age in blood and brain tissue (Bøstrand et al, 2022; Han et al, 2018; Marečková et al, 2020; Protsenko et al, 2021; Wolf et al, 2018; 2021) and with research suggesting associations between PTSD and MDD and transcriptomic age in blood (Carter et al, 2019; Cole et al, 2021; Kuan et al, 2021). This study extends this association to the brain transcriptome, demonstrating the robustness of these associations across the epigenome and tissue types.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are consistent with prior studies showing associations between multiple psychiatric phenotypes, including PTSD, AUD, MDD, and anxiety, and advanced DNAm age in blood and brain tissue (Bøstrand et al, 2022; Han et al, 2018; Marečková et al, 2020; Protsenko et al, 2021; Wolf et al, 2018; 2021) and with research suggesting associations between PTSD and MDD and transcriptomic age in blood (Carter et al, 2019; Cole et al, 2021; Kuan et al, 2021). This study extends this association to the brain transcriptome, demonstrating the robustness of these associations across the epigenome and tissue types.…”
Section: Discussionsupporting
confidence: 86%
“…Kuan et al (2021) reported significantly higher age‐adjusted RNA age estimates (using the Ren & Kuan, 2020 algorithm) in current PTSD cases compared to individuals without a current or prior PTSD diagnosis among 324 World Trade Center responders. Similarly, Cole et al (2021) found that individuals with MDD were more likely to have over‐estimated transcriptomic age relative to chronological age as compared to healthy controls; transcriptomic age was measured using a novel index derived from gene expression values obtained in peripheral blood mononuclear cells. In addition, one study calculated RNA age using microarray expression (not sequence) data from whole blood samples and found that depression during early adulthood was associated with advanced RNA age in African Americans (Carter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating gene expression of all participants, visual inspection of the PCA revealed no obvious grouping of samples (Fig S5). This is in line with rather subtle gene expression changes that one may expect in blood in the context of mental disorders [51,52]. Analyzing differential gene expression using DESeq2 [39], 13 significantly (FDR-corrected p ≤ 0.1) differentially expressed genes (DEGs) were identified which had a |l2fc| ≥ 0.3 with respect to SAD (Fig.…”
Section: Differential Gene Expression With Respect To Sad But Not Elasupporting
confidence: 66%
“…Beyond the impact of psychiatric symptoms on the morbidity and mortality associated with MDD, patients with depression also manifest a twofold to fourfold higher risk for cardiovascular disorders 160 , and have poorer outcomes during comorbid heart failure, stroke and peripheral artery disease [161][162][163] . Moreover, MDD is associated with exaggerated biological ageing: these individuals have premature decreases in leukocyte telomere length (a marker of cellular age that predicts several ageing-related diseases and early mortality) and increases in senescence-related gene transcription and molecular secretion patterns in physiological stress and inflammatory systems [164][165][166] . Dysregulation of the interactions among physiological stress systems that include inflammation, hypothalamic-pituitaryadrenal axis hyperactivity and metabolic dysregulation may partly underlie these associations [167][168][169] .…”
Section: ();mentioning
confidence: 99%